2007
DOI: 10.1179/174329007x186471
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of consolidated gamma titanium aluminides

Abstract: Microsized c-TiAl powders with composition of Ti-50Al (at.-%) and Ti-48Al-2Cr-2Nb (at.-%) were consolidated using a rapid consolidation technique called plasma pressure compaction (P 2 CH) to obtain samples with near gamma, duplex and fully lamellar microstructure. The consolidated samples exhibited minimal grain growth during consolidation, thereby retaining superior mechanical properties. The mechanical properties varied significantly with microstructure type, grain size and alloy composition. Samples with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…It can be observed that the workpiece material is mainly composed of α2+γ layered clusters at room temperature after hot isostatic pressing and aging treatment. In addition, there are equiaxed crystal γ and bright gray equiaxed crystal α2 in the lamellar microstructure, and a small amount of B element exists in the form of fine TiB2 whisker hard reinforcing phase, improving the materials mechanical properties [31]. Prior to the grinding test, the workpiece material was machined into a standard test piece (20 mm × 18 mm × 15 mm) suitable for ultrasonic device via the wire electrical discharge machining method.…”
Section: Workpiece Materialsmentioning
confidence: 99%
“…It can be observed that the workpiece material is mainly composed of α2+γ layered clusters at room temperature after hot isostatic pressing and aging treatment. In addition, there are equiaxed crystal γ and bright gray equiaxed crystal α2 in the lamellar microstructure, and a small amount of B element exists in the form of fine TiB2 whisker hard reinforcing phase, improving the materials mechanical properties [31]. Prior to the grinding test, the workpiece material was machined into a standard test piece (20 mm × 18 mm × 15 mm) suitable for ultrasonic device via the wire electrical discharge machining method.…”
Section: Workpiece Materialsmentioning
confidence: 99%
“…Also, the α 2 phase present in TiAl alloys is significantly decreased by Nb additions, decreasing its oxygen solubility [54]. Although Nb was primarily used for improving oxidation resistance [167], other high-temperature properties such as strength and creep resistance have been enhanced by the presence of Nb.…”
Section: Effect Of Alloy Modifications On the Oxidation Resistance Of Tialmentioning
confidence: 99%
“…Titanium aluminides show excellent high-temperature mechanical properties, as well as good corrosion and oxidation resistance, thus are great candidates for hightemperature applications [1,2]. Furthermore, their low density ( ∼ 3.7 g cm −3 ) [3] can be of great advantage for the production of gas turbine engines, exhaust valves and turbocharger rotors [4,5]. Despite the interesting high-temperature properties, some drawbacks hinder a wider application of titanium aluminides, especially when production costs are imperative.…”
Section: Introductionmentioning
confidence: 99%